(untitled) (Revista de Psicología, 2019)
The objective of this research was to examine the relation between the attachment perception and happiness in children between ages 7 and 8, who attend public schools. To evaluate the attachment perception, it was used the Kerns Security Scale Questionnaire (KSS) by Kerns, Keplac and Cole, 1996 (Argentinian adaptation by Richaud de Minzi, Sacchi and Moreno, 2001); and to evaluate happiness, it was used the analogical visual scale of joy/happiness (Oros, 2008). A univariate variable analysis was carried out (ANOVA). Significant results were obtained F Hotelling (2.104) = 3.14; p = .04. Children who got a high secure attachment presented high happiness percentages. These scientific contributions lead to mental health promotion programs for children that give priority to their healthy and functional development.